THE EFFECT OF APPLYING THE COSO INTERNAL CONTROL SYSTEM ON IMPROVING THE PROFESSIONAL SPECIALIZATION OF THE INTERNAL AUDITOR IN IRAQI COMMERCIAL BANKS - Mohammed Ali Al-Mahdi (Scholar Express Journals, 2022)
The research aims to Measuring the effect of applying the updated COSO Internal Control System in developing the professional specialization of auditors in banks listed on the Iraq Stock Exchange. This research was conducted in 10 banks registered in the Iraq Stock Exchange; the analytical method was used by distributing a questionnaire to the study sample and then conducting the necessary statistical analysis to complete the current study using the Statistical Package for Social Sciences (SPSS). The research reached the most important conclusions; the research revealed that there is a high awareness of the concept of the professional specialization of the internal auditor in Iraqi commercial banks, where the arithmetic mean was (4.15) when applying the updated COSO system under the control environment. The research reached the most important recommendations; Applying the strategy of professional specialization when applying COSO to improve the performance of the internal auditor when using electronic techniques in the implementation of audits.
Keywords: COSO; internal auditor; professional specialization; commercial banks